Analysing The Clinical Profile Of Influenza A(H1n1) Infected Patients : Oct 2018-Feb 2019, Ahmedabad, India (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction: Influenza virus is a common human pathogen that has caused serious respiratory illness and  death over the past century. In April 2009, a new strain of Influenza virus A H1N1,  commonly referred to as “swine flu”, began to spread in several countries around the world,  and India confirmed its first case on 16 May 16 2009. Aim: To study the clinical and epidemiological profile of Influenza A H1N1 cases at the Sheth  Vadilal Sarabhai General Hospital, Ahmedabad. Materials and Methods: Clinical epidemiological characteristics of Influenza A H1N1 cases from October2018 to  February 2019 were retrospectively, descriptively analyzed using data from isolation ward  and ICU at the Sheth Vadilal Sarabhai General Hospital, Ahmedabad. Data were Analyzed  using MS Excel software. Results: Out of 86 patients studied 36(51.16%) were males and 34(48.83%) were females. Almost  half of the patients(47.67%) were in the age group of 12-40 years. 6.9% mortality was found  irrespective of age group of the patients. Majority of the patients had  bronchopneumonia(39.53%) and bronchovascular prominence(41.86%), and very few of  them had lobar consolidation(8.13%). Here we had 63(73.25%) patients in category B and  23(26.74%) patients in category C, all the patients from category C required Ventilatory  support either Non invasive or invasive and 16(34.16%) of category B patients also required  ventilatory support.98.83% patients had complaint of fever on presentation. 36.04% had  breathlessness, 52.32% had coughing, 39.53% had sore throat, 30.23% had generalised weakness, 5.81 % had rhinitis, shock, blood in sputum,1.16% presented with diarrhea. None  of them presented with vomiting which is commonly found in other infections of influenza. 15.11% had hypertension, 10.46% had type 2 DM, 9.30% had IHD,10.46% had COPD, 5.81%  had hypothyroidism, 4.65% had tuberculosis, 2.32% had CVA. Out of 42 females 4 were  pregnant and 1 was post partum. Almost half of the patients(46.51%) required ventilatory  support in their course of hospitalization. Conclusion: On the basis of these findings, it can be safely hypothesized that prevalence of Influenza A  H1N1 is high in the younger population, and fever, cough and sore throat are the most  common symptoms with which the patients usually present. in course of hospitalization  half of the patients required ventilatory support which was weaned off later on. Associated  comorbid conditions particularly hypertension, diabetes, and COPD were associated with  longer duration of hospital stay and complications. Delay in hospital presentation and longer  duration of onset symptoms and administration of treatment were linked to poor outcome.  Despite of various efforts of government for awareness , patients fails to seek timely  medical advise. Over all if presented early after onset of the symptoms can lead to better  outcomes.
Keywords: Influenza virus; Influenza virus A H1N1; swine flu